1995
DOI: 10.3109/15563659509028915
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of Potassium Homeostasis in Poisoning

Abstract: Unless renal function is impaired or rhabdomyolysis is severe, hyperkalemia is a relatively uncommon metabolic complication of poisoning. In contrast, marked hypokalemia is a more common problem and may have serious sequelae. Most potassium disturbances in acute poisoning are due to disruption of extra-renal control mechanisms, notably the activity of Na+/K+ ATPase and K+ channels. Hypokalemia occurs because of increased Na+/K+ ATPase activity (e.g. beta 2 agonist, theophylline or insulin poisoning), competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 87 publications
0
29
0
2
Order By: Relevance
“…In this condition insulin shifts the resting potentials of the hypokalaemic rats fibres towards the equilibrium potential for Cl -ion (about -50 mV in skeletal muscle) potential at which a large fraction of the voltage dependent Na + channels are inactivated thus provoking fibre inexcitability and flaccid paralysis [12]. This may be a general mechanism by which conditions that cause release of insulin into the blood provoke flaccid paralysis, for instance in several disorders associated with chronic or transient hypokalaemia such as gastrointestinal and renal loss of K + ion [12], barium or chloroquine poisoning [4], liquorice intoxication [12], alcoholism [15], or in humans affected by the primary form of hypokalaemic periodic paralysis [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…In this condition insulin shifts the resting potentials of the hypokalaemic rats fibres towards the equilibrium potential for Cl -ion (about -50 mV in skeletal muscle) potential at which a large fraction of the voltage dependent Na + channels are inactivated thus provoking fibre inexcitability and flaccid paralysis [12]. This may be a general mechanism by which conditions that cause release of insulin into the blood provoke flaccid paralysis, for instance in several disorders associated with chronic or transient hypokalaemia such as gastrointestinal and renal loss of K + ion [12], barium or chloroquine poisoning [4], liquorice intoxication [12], alcoholism [15], or in humans affected by the primary form of hypokalaemic periodic paralysis [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…However the K concentration had recovered at 300 min despite the deterioration of renal function. Therefore, K level might also be increased by the disruption of extrarenal mechanisms such as ion channels 13) . As a mechanism of hyperkalemia caused by F toxicity, two in vitro studies showed that K effluxes from erythrocytes that are in contact with F, and F increases the intracellular Ca 2+ level, which is considered to trigger the activation of Ca 2+ -dependent K channels producing K effluxes 14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Die kapilläre Blutgasanalyse zeigte eine geringe respiratorische Partialinsuffizienz: pO 2 7,75 kPa, pCO 2 [11,12,29], vermuten andere einen direkten Einfluss der durch Theophyllin induzierten Hypokaliämie [11,13,14,18,19,27,28]. Hypokaliämien gelten neben Hypophosphatämi-en [5] und Hypernatriämien [10] als eigenständige Auslöser von Rhabdomyolysen [2]. Sie wurden in nahezu allen Fällen mit akuter Theophyllinüberdo-sierung und etwa der Hälfte der chronischen Intoxikationen gefunden [22].…”
Section: ❑ Labordiagnostikunclassified
“…Sie wurden in nahezu allen Fällen mit akuter Theophyllinüberdo-sierung und etwa der Hälfte der chronischen Intoxikationen gefunden [22]. Substanzen, die ähnlich dem Theophyllin die Aktivität der Na-K-ATPase erhöhen, wie ␤ 2 -Mimetika oder Insulin, können diese Hypokaliämie verstärken und dadurch zur Entstehung einer Rhabdomyolyse prädisponieren [2]. Gleiches gilt für Kaliumverluste anderer Art, wie zum Beispiel bei Diuretikatherapie oder gastrointestinalen Kaliumverlusten [23].…”
Section: ❑ Labordiagnostikunclassified